Pengaruh Balestra Terhadap Hasil Serangan dalam Olahraga Anggar Jenis Senjata Floret - Puji Astuti; Krisno Giovanni (Indra Institute Research & Publication, 2026)
This study aimed to analyze the effect of balestra technique training on attack performance in foil fencing among beginner athletes in Purwakarta Regency. An experimental method with a one group pretest posttest design was employed, involving eight novice fencers selected through purposive sampling. The Kuhadja Fencing Test (validity = 0.80; reliability = 0.81) was used for data collection. Training was conducted over six weeks (16 sessions). Data were analyzed using descriptive statistics, Liliefors normality test, homogeneity test, and paired t-test. Results showed a mean score increase from 53 to 62, but it was statistically non significant (t = 2.37 < t-critical = 3.18; α = 0.05), likely due to small sample size and limited training duration. Nevertheless, findings suggest balestra holds potential for further development with more rigorous methodology.